Malawi Economic Monitor, October 2015 : Adjusting in Turbulent Times - Record, Richard; Kandoole, Priscilla; Asim, Salman; Chilima, Efrem; Kalemba, Sunganani (World Bank, Washington, DC, 2015)
The Malawi economic monitor (MEM) provides an analysis of economic and structural development issues in Malawi. The aim of the publication is to foster better informed policy analysis and debate regarding the key challenges that Malawi faces in its endeavors to achieve high rates of stable, inclusive, and sustainable economic growth. The focus of the special topic is on the effectiveness of public spending on primary education and the means by which this can be improved. With more than half of Malawi’s population under the age of 18, the country faces significant challenges in its efforts to provide quality education to a growing population of students. Malawi also faces ongoing fiscal pressures, so there is a need to find ways to maximize the development impact within the limits of the finite resources available for investment in education. The MEM consists of two parts: part one presents a review of recent economic developments and a macroeconomic outlook. Part two focuses in greater depth on a special, selected topic relevant to Malawi’s development prospects.